Mixed impact aerobics for healthy living: effectiveness in students at risk for obesity - Andi Fepriyanto; Dian Helaprahara; Mohammad Hasan Basri; Ainur Rasyid; Nugroho Agung S (Bravo's: Jurnal Program Studi Pendidikan Jasmani dan Kesehatan, 2025)
Obesity is a serious global health problem among school-aged children. This study aims to assess the effectiveness of the mixed impact aerobic program in changing healthy living and reducing the risk of obesity in students. This study used a quasi-experimental pretest-posttest design with a control group. A total of 30 obese students were randomly selected as subjects. Measuring level obese wtih BMI and fitness level with Tes Kebugaran Siswa Indonesia (TKSI). The results of the study showed that in the experimental group there was a significant difference in physical fitness (p value = 0.009), while in the control group there was no significant difference (p value = 0.082). In addition, this program was successful to improve healthy lifestyle behaviors. It can be concluded that the provision of mixed impact aerobic can improve healthy lifestyles by improving students' phyisical fitness of obese students